Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/ma15217738
|View full text |Cite
|
Sign up to set email alerts
|

Hemolysis-Inspired, Highly Sensitive, Label-Free IgM Detection Using Erythrocyte Membrane-Functionalized Nanomechanical Resonators

Abstract: Immunoglobulin detection is important for immunoassays, such as diagnosing infectious diseases, evaluating immune status, and determining neutralizing antibody concentrations. However, since most immunoassays rely on labeling methods, there are limitations on determining the limit of detection (LOD) of biosensors. In addition, although the antigen must be immobilized via complex chemical treatment, it is difficult to precisely control the immobilization concentration. This reduces the reproducibility of the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Our research findings concluded that there was a significant increase in phagocyte and lysozyme activities in the group fed diet containing 1.5 g IMB/kg diet, which could be a result of increased release from the lysosomes or the proliferating phagocytes. Additionally, IgM is the first antibody the body makes when it fights a new infection (Lee et al, 2022). Also, IgM plays several crucial roles in maintaining B cell survival and lymphoid tissue architecture, which was increased significantly in the 1 and 1.5 g IMB/kg diet‐fed groups (Michaud et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Our research findings concluded that there was a significant increase in phagocyte and lysozyme activities in the group fed diet containing 1.5 g IMB/kg diet, which could be a result of increased release from the lysosomes or the proliferating phagocytes. Additionally, IgM is the first antibody the body makes when it fights a new infection (Lee et al, 2022). Also, IgM plays several crucial roles in maintaining B cell survival and lymphoid tissue architecture, which was increased significantly in the 1 and 1.5 g IMB/kg diet‐fed groups (Michaud et al, 2020).…”
Section: Discussionmentioning
confidence: 99%